Preserving Gastronomic Heritage through Culinary Entre-preneurship - Edouard Aryadi Supriyadi; Sony Heru Priyanto; Nur Widianto (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2026)
Gastronomic heritage has become an important component in strengthening cultural identity and tourism destination competitiveness. However, previous studies have primarily emphasized gastronomy as a tourism attraction, while the role of culinary entrepreneurs in preserving gastronomic heritage remains underexplored. This study aims to examine how culinary entrepreneurship contributes to preserving gastronomic heritage through a phenomenological approach. The research was conducted at Singkong Keju D-9 in Salatiga, Central Java, involving the business owner as the main participant. Data were collected through in-depth interviews, observations, and documentation, and analyzed using phenomenological data analysis. The findings reveal that culinary entrepreneurship preserves gastronomic heritage through four interconnected practices: revalorizing local food, preserving culinary authenticity, knowledge sharing, and community empowerment. These practices collectively transform local food into cultural and tourism assets while maintaining product authenticity, transmitting culinary knowledge, empowering local communities, and strengthening the identity of gastronomic destinations. The study further demonstrates that culinary entrepreneurs serve not only as economic actors but also as custodians and transmitters of gastronomic heritage. This research contributes to gastronomic tourism literature by proposing a research findings framework that explains the relationship between entrepreneurial practices and gastronomic heritage preservation, providing practical implications for developing sustainable gastronomy tourism destinations based on local cultural heritage.